2017
DOI: 10.1002/app.46096
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of pyridine‐based polyether polyurethanes by the Alternaria tenuissima fungus

Abstract: The scope of the present work is to study the biodegradability behavior of several novel heterocyclic poly(ether urethanes) when their hard segments are subjected to exposure to the Alternaria tenuissima fungus. The heterocyclic poly(ether urethanes) were chain-extended with various pyridine derivatives that had different functional groups placed in different positions on the pyridine rings. Different ratios of the reactive components were also used. The measurements obtained by the use of the attenuated total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Neoscytalidium hyalinum/dimidiatum and Alternaria porri / destruens are completely novel. Alternaria tenuissima has been isolated from oil contaminated water but was strongly inhibited by crude oil presence 79 and has also been reported to degrade polyurethanes, an important compound in plastic degradation and recycling 80 , 81 . Alternaria destruens is a beneficial soil microbe that can promote the growth of plants 82 ; this fungus then, can be further investigated for its benefits of vegetative growth in heavily contaminated soil as in Marac.…”
Section: Discussionmentioning
confidence: 99%
“…Neoscytalidium hyalinum/dimidiatum and Alternaria porri / destruens are completely novel. Alternaria tenuissima has been isolated from oil contaminated water but was strongly inhibited by crude oil presence 79 and has also been reported to degrade polyurethanes, an important compound in plastic degradation and recycling 80 , 81 . Alternaria destruens is a beneficial soil microbe that can promote the growth of plants 82 ; this fungus then, can be further investigated for its benefits of vegetative growth in heavily contaminated soil as in Marac.…”
Section: Discussionmentioning
confidence: 99%
“…Stepien et al found that three bacteria and one yeast ( Table 6) could degrade commercial polyether PUR films (Tecoflex R ) and cause a weight loss of 2.8-10.5% within 5 months (Stepien et al, 2017). Oprea et al assessed the biodegradability of pyridine-based polyether PUR elastomers by a fungus Alternaria tenuissima, and found that the fungus could decrease the mechanical properties and deteriorate the surface morphology after 60 days (Oprea et al, 2018).…”
Section: Purmentioning
confidence: 99%
“…Alternaria species have already been described for PU degradation. For example, a strain of A. tenuissima was reported as active on pyridine-based polyether PU (Oprea et al, 2018). Alternaria solani, isolated from soil, showed degradation activity towards a polyester PU (Ibrahim, 2009).…”
Section: Discussionmentioning
confidence: 99%